Relationship Between Single-Leg Vertical Jump and Drop Jump Performance, and Return to Sports After Primary Anterior Cruciate Ligament Reconstruction Using Hamstring Graft - Shunsuke Ohji; Junya Aizawa; Kenji Hirohata; Takehiro Ohmi; Tomoko Kawasaki; Hideyuki Koga; Kazuyoshi Yagishita (North American Sports Medicine Institute, 2024)
# Background After anterior cruciate ligament reconstruction (ACLR), asymmetry is likely to persist in single-leg (SL) vertical jump and drop jump performance than in SL hop distance. However, its relationship with the return to sport (RTS) remains unclear. # Hypothesis/Purpose This study aimed to determine the association between vertical jump performance after primary ACLR using hamstring tendon autograft and RTS at a pre-injury competitive level. # Study design Cross-sectional study # Methods Patients who underwent primary ACLR using hamstring tendon autograft were recruited for this study. Participants who returned to pre-injury competition after ACLR were recruited at least eight months postoperatively. Knee condition was assessed, including joint laxity, range of motion, muscle strength, and knee pain intensity during sports activities. Performance variables were also assessed, including SL hop distance, jump height in SL vertical jump, and reactive strength index (RSI; jump height/contact time) in SL drop jump. Participants were asked to subjectively report whether they had returned to the same level of competition as pre-injury and their perceived sport performance intensity. Those who answered "Yes" to the dichotomous question and had a postoperative subjective athletic performance of \> 80% were categorized into the Yes-RTS group. The primary outcome was the ability to achieve RTS at the preinjury level. # Results Sixty-five patients (female, 35; male, 30) at 13.0 (13.0) \[median (interquartile)\] months after ACLR participated in this study. Thirty-nine (60%) were assigned to the Yes-RTS group. Regarding knee conditions, the No-RTS group had a significantly higher knee pain intensity, as assessed using a numerical rating scale (p\<0.001, effect size -0.45). In the performance tests, the No-RTS group exhibited a significantly lower limb symmetry index of RSI during the SL drop jump compared to the Yes-RTS group (p=0.002, effect size 0.81). # Conclusion Patients unable to achieve RTS after primary ACLR using hamstring grafts are more likely to exhibit asymmetric performance during the SL drop jump test, suggesting the significance of assessing jump symmetry when evaluating post-ACLR rehabilitation success. # Level of Evidence 3c